The Impact of Materials Management on Profitability of Manufacturing Companies in Ethiopia: The Case of Walia Steel Industry PLC - Jagadish Brahma Goulap; Yohannes Workeaferahu Elifneh; Abera Zerihun Belew (International Journal of Engineering and Management Research, 2022)
Recently, in the dramatically growing digital world, the management of materials plays a critical role in the profitability of manufacturing companies. This study focuses on the impact of materials management on profitability of manufacturing companies in Ethiopia with a particular reference to Walia Steel Industry PLC. The main objective of the study is to detect the problems of materials management that can result in achieving organizational profitability if corrected properly. Relevant data was gathered through self-administered structured questionnaires and open-ended questions and analysis was made based on primary data generated via five point Likert scale using SPSS version 23. A cross-sectional data model was used in the study. The study adopted both explanatory and descriptive research designs in integration with commonly used mixed research methods. Validity and reliability of the study was also tested using SPSS V-23. The findings revealed that there was positive and significant association between effective materials management dimensions and firm’s profitability which was supported by interdepartmental collaboration among materials related departments such as inventory, procurement and storage managements. The main problems faced in materials management of the selected steel industry includes the shortage of raw materials due to foreign currency problem and COVID-19 pandemic, shortage of skilled personnel, unsteady power supply, weak materials management practices due to weak interdepartmental coordination of the firm. The role and benefits of materials management dimensions should be examined and outlined for further investigation. Recommendations were made for the focal firm to make the materials management system to be computerized, to arrange training programs, to hire skilled personnel and to arrange employee’s motivation system. Recommendations also made for the government to provide adequate infrastructures such as available domestic raw materials, steady power supply, and sufficient water supply and so on to assist manufacturing firms. Keywords: Materials Management, Procurement Management, Inventory Management, Storage Management, Interdepartmental Collaboration, Organizational Profitability